Steady Boundary Layer Flow Of Nanofluid With Microorganism - Amirsom, Nur Ardiana (2020)
In this thesis, an analysis of two and three dimensional laminar convective boundary layer flow of a nanofluid with microorganism is investigated. It involves two and three dimensional laminar convective external boundary layer flow with heat and mass transfer under various physical configurations as well as geometries.